Investigating the effect of a nap following experimental trauma on analogue PTSD symptoms - Ines Wilhelm (Nature Portfolio, 2021)
Abstract Cognitive models assume that the incomplete integration of a traumatic experience into the autobiographical memory results in typical symptoms associated with post-traumatic stress disorder (PTSD) such as intrusive re-experiencing. Sleep supports the integration of new experiences into existing memory networks through memory consolidation. In fifty-six females, we investigated whether a 90-min daytime nap (n = 33) compared to a wake period (n = 23) after being exposed to an experimental trauma (i.e. a trauma film) prevents PTSD analogue symptoms. Intrusive memories were recorded for seven days using a diary, overall PTSD symptoms were assessed using the Impact of Event Scale (IES-R) and affective response to trauma cues were measured one week after experimental trauma. The two groups did not differ in any of the analogue PTSD symptoms. However, participants obtaining rapid eye movement (REM) sleep in the nap experienced less distressing intrusive memories. Moreover, the duration of REM sleep and slow wave activity was negatively correlated with analogue PTSD symptoms. Our findings suggest that even a short sleep period after experimental trauma can play a protective role in trauma memory formation but only if the nap contains REM sleep. Our data provide additional evidence for a critical role of REM sleep in PTSD development.